Modification of stock tray in the manufacture of Aramany class IV obturator maxillofacial prosthesis: Modifikasi stock tray pada pembuatan prostesis maksilofasial obturator klas IV Aramany - Sutrisman, Andry; Syafrinani; Ritonga, Putri Welda Utami (Makassar Dental Journal, 2024)
A maxillofacial prosthesis (MFP) was inserted to replace the hard and soft tissues and teeth lost after maxillectomy surgery in a case of ameloblastoma. Facial deformity, soft tissue invasion and limited mouth opening caused difficulties in the moulding pro-cess. This article presents anatomical moulding modifications to improve treatment success in MFP placement. A 19-year-old female came to RSGM USU referred from RSU Murni Teguh for immediate post-surgical placement of a maxillary closure device. The patient was diagnosed as ameloblastoma with facial deformity, and tissue invasion on the left side. The patient's facial con-dition was asymmetrical and difficult to open the mouth, making impression difficult. Anatomical impression was performed with modification and selection of appropriate stock tray, followed by fabrication of surgical obturator MFP and Class IV Aramany in-terim as prosthetic rehabilitation device. It was concluded that MFP insertion in post-maxillectomy patients with impression dif-ficulties, modification of the stock tray moulding spoon can determine the success of treatment.